The rise of the Enterococcus: beyond vancomycin resistance - Arias, Cesar A.; Murray, Barbara E. (Nature reviews. Microbiology, 2012)
Key Points Enterococci are some of the most versatile organisms found to infect hospitalized patients. The epidemiology of enterococcal infections has evolved since the emergence of these pathogens and has seen the rise of Enterococcus faecium as a nosocomial pathogen with serious clinical implications. The effect of antibiotics on the microbiota of the gastrointestinal tract and subsequent alterations in the regulation of the gut immune system can favour colonization by multidrug-resistant enterococci. Enterococcal genomes are extremely malleable, with the ability to exchange large fragments of chromosomal DNA. In addition, the lack of CRISPR (clustered regularly interspaced short palindromic repeats) elements has a potential role in the adaptation of hospital-associated enterococci. Specific pathogenicity factors contribute to the ability of enterococci to produce disease and/or survive in the gastrointestinal tract of mammals. The major factors include secreted and cell surface-associated determinants. Antibiotic resistance is widespread for the anti-enterococcal antibiotics that are most commonly used in clinical practice, and the mechanisms of resistance for many of these antibiotics are known. These antibiotics include ampicillin, linezolid, daptomycin and quinupristin–dalfopristin, and there is also high-level resistance to aminoglycosides. Such resistances have important therapeutic implications. Arias and Murray discuss the factors that may have contributed to the rise of enterococci as nosocomial pathogens, with an emphasis on the epidemiology and pathogenesis of these species and their mechanisms of resistance to the most relevant anti-enterococcal agents used in clinical practice. The genus Enterococcus includes some of the most important nosocomial multidrug-resistant organisms, and these pathogens usually affect patients who are debilitated by other, concurrent illnesses and undergoing prolonged hospitalization. This Review discusses the factors involved in the changing epidemiology of enterococcal infections, with an emphasis on Enterococcus faecium as an emergent and challenging nosocomial problem. The effects of antibiotics on the gut microbiota and on colonization with vancomycin-resistant enterococci are highlighted, including how enterococci benefit from the antibiotic-mediated eradication of Gram-negative members of the gut microbiota. Analyses of enterococcal genomes indicate that there are certain genetic lineages, including an E. faecium clade of ancient origin, with the ability to succeed in the hospital environment, and the possible virulence determinants that are found in these genetic lineages are discussed. Finally, we review the most important mechanisms of resistance to the antibiotics that are used to treat vancomycin-resistant enterococci.